Human and Planetary Health The urgency to integrate into One Health - van laarhoven, Kees (Radboud University Press, 2023)
In his professional journey, travelling through an upcoming field of surgery with apparently unlimited possibilities, Kees van Laarhoven witnessed major milestones and breakthroughs. Already as a medical student, he was amazed by surgical courage. During residency, he experienced hard work, diligence and perseverance of surgical professionals. Today as a surgeon with over 25 years of clinical experience he now looks at pieces of art in surgery with professionals compassionately bringing hope to patients.But he also sees inconvenient truths in our healthcare system, with patients evolving from one predictable and preventable disease to the next and with professionals following disease trends rather than applying their knowledge to redirect disease into health. The modern disease-oriented care system becomes undesirable and unsustainable. And there are more inconvenient truths that have progressed rather than diminished in time. Healthcare is not easily accessible to the major half of the global population and for those who have access, with a growing global population, healthcare may become unaffordable in the future. Moreover, from an environmental perspective, both human and planetary health are compromised and ask for a 'One Health' approach. Being fascinated by the questions of how and why did this all happen, Kees van Laarhoven took up a scientific survey to comprehend and learn how things still can be changed. He found that clear solutions are there! Please join him on his journey.